Root-specific Reduction of Cytokinin Perception Enhances Shoot Growth in Arabidopsis thaliana. (2nd February 2022) - Monden, Kota; Kojima, Mikiko; Takebayashi, Yumiko; Suzuki, Takamasa; Nakagawa, Tsuyoshi; Sakakibara, Hitoshi; Hachiya, Takushi
Abstract: Previous studies suggest that root-derived cytokinins (CKs) contribute to shoot growth via long-distance transport; therefore, we hypothesized that an increase in root-derived CKs enhances shoot growth. To verify this, we grafted Arabidopsis Col-0 (wild type, WT) scion onto rootstock originated from WT or a double-knockout mutant of CK receptors Arabidopsis histidine kinase 2 ( AHK2 ) and AHK3 ( ahk2-5 ahk3-7; ahk23 ) because this mutant overaccumulates CKs in the body probably due to feedback homeostasis regulation. The grafted plants (scion/rootstock: WT/WT and WT/ ahk23 ) were grown in vermiculite pots or solid media for vegetative growth and biochemical analysis. The root-specific deficiency of AHK2 and AHK3 increased root concentrations of trans -zeatin (tZ)-type and N 6 -(Δ 2 -isopentenyl) adenine (iP)-type CKs, induced CK biosynthesis genes and repressed CK degradation genes in the root. The WT/ ahk23 plants had significantly larger shoot weight, rosette diameter and leaves area than did the WT/WT plants. Shoot concentrations of tZ-type CKs showed increasing trends in the WT/ ahk23 plants. Moreover, the root-specific deficiency of AHK2 and AHK3 enhanced shoot growth in the WT scion more strongly than in the ahk23 scion, suggesting that shoot growth enhancement could occur through increased shoot perception of CKs. In the WT/ ahk23 shoots compared with the WT/WT shoots, however, induction of most of CK-inducible response regulator genes was not statistically significant. Thus we suggest that the root-specific reduction of CK perception enhances shoot growth only partly by increasing the amount of root-derived tZ-type CKs and their perception by shoots. The unknown mechanism(s) distinct from CK signaling would also be involved in the shoot growth enhancement.